Cyber-physical threat detection platform designed for healthcare systems - Suciu, George (Array, 2020)
Hospitals are responsible for delivering healthcare services to patients in need. These services are large and complex and get affected by multiple interacting actors, such as doctors, nurses, patients, citizens, medical suppliers, health insurance providers. Lately, hospitals around the world are one of the main targets when it comes to terrorist attacks, the cyber realm being the principal source. The healthcare sector is particularly vulnerable due to heavy involvement in patient personal and health information, time constraints, and complex day-to-day operations. In addition to cyber-threats, physical threats are increasingly growing and even healthcare facilities are not immune to them. Malicious intended people created cyber threatening attacks with the purpose to systematically collect evidence against the healthcare system, to advocate for the end of such attacks, and to endanger people's lives or to use the stolen personal data for bad intended actions. Henceforth it is necessary to build a platform that will get alerts and incidents at a fast pace in real-time to prevent any casualties at low cost. SAFECARE project aims to offer protection to hospitals and increase the compliance for the European regulations and security regarding ethics and privacy for health services. This paper presents a solution that will enhance security in hospitals. The primary platform will be built based on a BTMS (Building Threat Monitoring System) where events, incidents, and alerts will be transmitted by sensors from hospital rooms in real-time. Several scenarios were thought to simulate different types of attacks against hospitals and according to the scenarios, various prototypes will be built for assuring the security of the personal and patients from various hospitals.